Faktor-faktor yang mempengaruhi perilaku sosial suporter Perssin Sinjai di Kabupaten Sinjai - Arifuddin Usman; Herman Herman (Seminar Nasional LP2M UNM, 2019)
This research is descriptive research type. This study aims to determine; factors influencing social behavior of Perssin Sinjai supporters in Sinjai District. The population is the board and supporters of Perssin Sinjai of Sinjai Regency. The sample used is the board and supporters Perssin Sinjai District Sinjai amounted to 30 people. The technique of determining the sample is by purposive sampling. Data analysis technique used is descriptive analysis of frequency. The results showed that factors influencing social behavior of Perssin Sinjai supporters in Sinjai District consisting of willingness of supporters, loyalty, pride, feeling, need each other, actively participate in activities, actively involved in the board and participate in giving donations in good category value of 63%.